Optimalisasi Priority Pada Organ at Risk (OAR) Kanker Nasofaring Menggunakan Teknik Intensity Modulated Radiation Therapy (IMRT) - Relis, Septya Annisa; Dian Milvita; Fiqi Diyona (Jurnal Fisika Unand, 2025)
Optimization of priority on Organ At Risk (OAR) of nasopharyngeal cancer using Intensity Modulated Radiation Therapy (IMRT) technique has been conducted. The research was conducted using 5 images of nasopharyngeal cancer patients processed using Treatment Planning System (TPS) Eclipse software at Andalas University Hospital. The purpose of this study was to determine the priority value of Planning Target Volume (PTV) and OAR by analyzing the value of Conformity Index (CI), Homogeneity Index (HI) and OAR radiation dose on the Dose Volume Histogram (DVH) curve based on 6 planning variations. The planning variations used are priority values on PTV 100,110,120,130,140 and 150. Variations of priority values on OAR 40,50,60,70,80 and 90. The results of the study obtained the optimal priority value for each nasopharyngeal cancer patient's initials are S, J, SS, ED and B for PTV which is 120. On the brain stem OAR is 103, 85, 90, 103, and 85. The spinal cord OAR is 82,88,85,85, and 85. The OAR of the eye lens was 58,100,90,85 and 90. The OAR of the eye was 65,90,70,0 and 80. The OAR of the mandible was 72,100,90,99 and 80. Analysis of CI and HI values based on the International Commission on Radiation Units and Measures (ICRU) Report 62 and 83. The radiation dose to the OAR was verified based on the Quantitative Analysis of Normal Tissue Effect in the Clinic (QUANTEC) standard. The priority value obtained in this study will be a reference for medical physicists in making radiotherapy planning.